Indigofera suffruticosa Mill. (Anil): Plant Profile, Phytochemistry, and Pharmacology Review - Janaina K. L. Campos; Tiago F. da S. Araújo; Thaíse G. da S. Brito; Ana P. S. da Silva; Rebeca X. da Cunha; Mônica B. Martins; Nicácio H. da Silva; Bianka S. dos Santos; César A. da Silva; Vera L. de M. Lima (Advances in Pharmacological Sciences)
Indigoferasuffruticosa Mill. (Fabaceae) is known as anil or anileira and also with other names, due to the production of a blue pigment, which is commonly used for yarn dyeing. It is distributed in some states of Brazil (Pernambuco, Paraíba, Mato Grosso, São Paulo, Bahia, Pará, and others) and is used in the popular medicine as a febrifuge, antispasmodic, diuretic, abortive, analgesic, purgative, or soothing agent against stomach and urinary problems, jaundice, and ulcers and also as an insecticide. In addition, I. suffruticosa can be used as animal feed. This review aimed at providing important data on the botanical, distribution, ethnopharmacology, phytochemical, pharmacological, and toxicity of I. suffruticosa based on the scientific literature. Information on I. suffruticosa was gathered via the Internet (from Elsevier, NCBI, and Sci-Hub) and libraries in the period from February to March 2016. More than 40 chemical compounds have been identified and a few compounds isolated, and the main origins are the essential oils, organic extracts, and aqueous extracts of different parts of the plant. I. suffruticosa and its active compounds possess wide pharmacological actions in the literature, such as anti-inflammatory, antibacterial, antifungal, antioxidative, antitumor, antimutagenic, anticonvulsant, gastroprotective, and hepatoprotective activities. Therefore, as an important traditional popular medicine, further studies on I. suffruticosa are required for the development of new drugs and therapeutics for various diseases.